Life, love and the pursuit of happiness - Hill, Sandra (Fiction writer) (Hill, Sandra (Fiction writer) Bell Sound novel., 2019)
Merrill Good knows there are many different kinds of exciting. There<U+2019>s the adrenaline rush he experienced during his years in the military. There<U+2019>s the thrill of starting up his own treasure hunting company. But topping them all is the surge of exhilaration he feels every time Delilah Jones crosses his path. Smart, voluptuous, and outspoken, Delilah is a bombshell with a secret that could explode at any moment. Since Delilah moved to Bell Cove to take over her great-uncle<U+2019>s Elvis-themed diner and motel, the locals have been nothing but friendly. And that<U+2019>s a problem. The moment someone gets close enough to figure out her ex-con past, her future will be jeopardized. But keeping Merrill at arm<U+2019>s length isn<U+2019>t easy when the rest of her body has other ideas. Add to the mix Delilah<U+2019>s little girl who fashions herself “Little Orphan Annie,” a former showgirl grandmother with a gambling problem, a whole town full of quirky matchmakers, and there<U+2019>ll be fireworks long after the Fourth of July . . .